ANALEPSIS AND PROLEPSIS AS EPISTEME IN MARGARET LAURENCE’S THE DIVINERS (International Journal of Food and Nutritional Sciences, 2022)
Margaret Lawrence, in her fiction distorts time to expose the background of the story. The time frame of The Diviners is less than a year, but the entire story covers forty-seven years in the life of the protagonist. To present the events of the period, Margaret Lawrence adopts the technique of prolepsis and analepsis.